1993
DOI: 10.1055/s-2008-1053826
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorielle Gliome: Analyse klinischer und zeitlicher Parameter in 163 Fällen

Abstract: 163 cases of supratentorial astrocytomas and glioblastomas were evaluated retrospectively after close-meshed observation and treatment. We attached the greatest importance to the reevaluation of already known prognostic parameters and to the temporal analysis of the course of gliomas. We could confirm the influence of the histologic grade on the survival time. Histologic grading by means of immunohistochemistry proved to be more precise than grading only by means of HE staining. Furthermore, the patient's age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Thirty-two studies were identified between 1990 and 2012 examining EOR and high-grade glioma patient outcomes (Shibamoto et al, 1990; Vecht et al, 1990; Hollerhage et al, 1991; Phillips et al, 1991; Sandberg-Wollheim et al, 1991; Curran et al, 1992; Duncan et al, 1992; Prados et al, 1992; Dinapoli et al, 1993; Huber et al, 1993; Simpson et al, 1993; Jeremic et al, 1994; Warnke et al, 1994; Nitta and Sato, 1995; Barker et al, 1996; Kowalczuk et al, 1997; Keles et al, 1999, 2006; Buckner et al, 2001; Lacroix et al, 2001; Levin et al, 2002; Puduvalli et al, 2003; Tortosa et al, 2003; Lamborn et al, 2004; Brown et al, 2005; Pope et al, 2005; Stark et al, 2005; Ushio et al, 2005; Nomiya et al, 2007). Most, but not all, studies used standard WHO grading criteria; other grading systems were utilized in a minority of reports (Dinapoli et al, 1993; Levin et al, 2002; Stark et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two studies were identified between 1990 and 2012 examining EOR and high-grade glioma patient outcomes (Shibamoto et al, 1990; Vecht et al, 1990; Hollerhage et al, 1991; Phillips et al, 1991; Sandberg-Wollheim et al, 1991; Curran et al, 1992; Duncan et al, 1992; Prados et al, 1992; Dinapoli et al, 1993; Huber et al, 1993; Simpson et al, 1993; Jeremic et al, 1994; Warnke et al, 1994; Nitta and Sato, 1995; Barker et al, 1996; Kowalczuk et al, 1997; Keles et al, 1999, 2006; Buckner et al, 2001; Lacroix et al, 2001; Levin et al, 2002; Puduvalli et al, 2003; Tortosa et al, 2003; Lamborn et al, 2004; Brown et al, 2005; Pope et al, 2005; Stark et al, 2005; Ushio et al, 2005; Nomiya et al, 2007). Most, but not all, studies used standard WHO grading criteria; other grading systems were utilized in a minority of reports (Dinapoli et al, 1993; Levin et al, 2002; Stark et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, four studies found EOR to only be associated with increased patient survival in multivariate analysis, but not univariate analysis. Conversely, 11 non-volumetric studies ( N  = 1800, range 75–357 patients) demonstrated no overall survival benefit associated with increased EOR using either univariate or multivariate analysis (Table 3; Hollerhage et al, 1991; Phillips et al, 1991; Sandberg-Wollheim et al, 1991; Duncan et al, 1992; Prados et al, 1992; Huber et al, 1993; Kowalczuk et al, 1997; Levin et al, 2002; Puduvalli et al, 2003; Tortosa et al, 2003; Oszvald et al, 2012). Potential confounders such as use of chemotherapy and radiation therapy varied widely between publications, but did not differ significantly among patients receiving greater or lesser EOR in any individual series.…”
Section: Resultsmentioning
confidence: 99%
“…Si bien la mayoría de las comunicaciones sobre resección de gliomas de alto grado muestra benefi cio en la sobrevida 2,6,20,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] , algunos trabajos no encuentran benefi cio signifi cativo [47][48][49][50][51][52][53][54][55][56] .…”
Section: Discussionunclassified
“…Seventeen nonvolumetric extent of resection studies (n ¼ 4992, range 86-949 patients) demonstrated a survival benefit associated with increased extent of resection using univariate or multivariate analyses) [3][4][5][6][7]11,16,18,19,25,26,28,30,31,[33][34][35]. Conversely, 11 nonvolumetric studies (n ¼ 1800, range 75-357 patients) demonstrated no overall survival benefit associated with increased extent of resection using either univariate or multivariate analysis [8][9][10]14,17,20,[22][23][24]29,34]. Of the 14 studies that utilized multivariate analysis to control for age, performance status, and use of adjuvant therapy, only one such analysis [6] subsequently rendered extent of resection nonsignificant.…”
Section: Key Pointsmentioning
confidence: 99%